Lesbian adolescents' narratives of identity : a participatory photovoice project - Zway, Maia Sarah (Department of Psychology, 2016)
Lesbian identities in South Africa have largely been framed within a risk paradigm, with a focus on adolescents' experiences of homophobic victimisation in schools and black lesbian women being victims of 'corrective rape'. This framing of lesbian identities within a risk paradigm is problematic, as it erases the multi-dimensionality of lesbian lives and identities. This study aimed to shift away from a risk paradigm and allow young lesbian adolescents to represent their own lives and identities. This study therefore investigated how young lesbian and bisexual women chose to represent their lives and identities through the method of Photovoice, and how the stories they told challenged or maintained dominant narratives about young people of diverse sexualities. Fourteen black, Xhosa-speaking adolescents between the ages of thirteen and seventeen participated. Twelve participants identified as butch lesbians and two identified as bisexual. The study used Photovoice, a participatory action research (PAR) method. The participants were trained in photography and took photographs that represented a story that they wanted to tell about their lives, and created a written narrative (photostory) to accompany their photographs. They also participated in focus groups and individual interviews. The Photovoice process culminated in a public exhibition of the participants' photographic work. The focus group transcripts, interview transcripts, photostories, and photographs were analysed using thematic narrative analysis. Five main narrative themes emerged: Narrating 'tomboy' childhoods; Clothing as a symbol of identity; Negotiating butch identity; Constructions of safety, violence, and community; and finally Alienation and finding affirming spaces. Recommendations and implications of the findings are discussed. In particular, the findings point to the importance of the use of participatory methods with young people.